2015
DOI: 10.1039/c5cp02882e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical exploration of the nanoscale host–guest interactions between [n]cycloparaphenylenes (n = 10, 8 and 9) and fullerene C60: from single- to three-potential well

Abstract: The nanoscale host-guest interactions between [n]cycloparaphenylene ([n]CPP; n = 10, 8 and 9) nano-ring and fullerene C60 were explored theoretically. It is found that relatively small variations in the sizes of the [n]CPP host lead to very significant changes in encapsulation property toward the fullerene C60 guest. Expectedly, one stable inclusion-configuration of [10]CPP⊃C60 and one floating-configuration of [8]CPP⊃C60 are located on the potential surfaces of the two complexes, respectively. Unexpectedly, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 45 publications
4
38
0
2
Order By: Relevance
“…The ability of this density functional to predict and explain the supramolecular chemistry of carbon nanohoops and fullerenes at van der Waals distances is very encouraging . All the geometric configurations were fully optimized at the M06‐2X/6‐31G(d) level in vacuum and solvent (toluene), respectively. To ensure the most stable structure being obtained for each of the complexes, the fullerene is placed inside O 6 ‐corona[6]arene ring and rotated stepwisely along the long axis of C 70 , and then, the most stable structure obtained is selected for further analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of this density functional to predict and explain the supramolecular chemistry of carbon nanohoops and fullerenes at van der Waals distances is very encouraging . All the geometric configurations were fully optimized at the M06‐2X/6‐31G(d) level in vacuum and solvent (toluene), respectively. To ensure the most stable structure being obtained for each of the complexes, the fullerene is placed inside O 6 ‐corona[6]arene ring and rotated stepwisely along the long axis of C 70 , and then, the most stable structure obtained is selected for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Encouragingly, because of their good selectivity, high efficiency, and even stimuli responsiveness, host‐guest interaction systems have played significant roles in the development of advanced supramolecular materials and devices . Especially, for a nanoscale system, host‐guest interaction may result in novel nanohybrid with new properties and unique functions, which is maybe very different from the individual host or guest molecule . The well‐designed host‐guest complexes have been used to construct various supramolecular function systems, such as novel host systems that can reversibly capture and release guest molecules in a controllable manner …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, newly developed density functional have been reported that explicitly include a dispersion correction, such as M06, B97D, van der Waals density functional (vdW‐DFT), and DFT‐D3 (denoted by the suffix “‐D3”) . In this work, Grimme's DFT‐D3 method, which takes into account the hybridization states of the interacting atoms and provides an empirical dispersion correction for DFT, is used for the present noncovalent stacking because it can be applied economically to predict and analyze large structures and can therefore be used conveniently for supramolecular systems . All considered stacking structures and counterpart monomers were fully optimized at the B3LYP/6‐31G(D, P)/MIDI!…”
Section: Calculation Details and Methodsmentioning
confidence: 99%
“…As Hobza pointed, although covalent interactions determine the primary structure of a molecule, the noncovalent interactions are responsible for the tertiary and quaternary structure of a molecule and create the fascinating world of the 3D architectures of supramolecular systems, so dose for those of carbon‐nanostructures. For an instance, driven by convex‐concave π–π noncovalent interactions, quite stable host–guest carbon‐base “peapod” structures can be formed with CNRs or CNTs and fullerenes or endohedral metallofullerenes, and those nanoscale systems possess novel nano‐hybrid with interesting properties and unique functions, which may be very different from the individual components. Using first principle and molecular mechanics methods, our group investigated the noncovalent interaction between nanodiamonds, and found that the binding model is face(111)‐face(111) van der Waals force .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Ther ing moiety should have ar igid circular shape and be able to include the spherical molecule into its cavity through attractive interactions.T ypical planet moieties are [60]fullerene (C 60 )a nd other fullerenes,o wing to their spherical shape and the presence of p-electrons enhancing molecular association. [1][2][3] Ther ing moiety should have ar igid circular shape and be able to include the spherical molecule into its cavity through attractive interactions.T ypical planet moieties are [60]fullerene (C 60 )a nd other fullerenes,o wing to their spherical shape and the presence of p-electrons enhancing molecular association.…”
mentioning
confidence: 99%